Multimodal Discourse Analysis for teaching English as a Second Language - et. al., Kawa Abdul–Kareem Sherwani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
New technological developments have boosted the use of different modes or semiotic resources; social changes and developments, on the other hand, have changed the process of meaning making because discourse shapes and is shaped by social practices. Semiotic resources are used in communication (language, sound, gestures, facial expressions … etc) and this has impact and reflections on the methods of teaching. Literacy is not only about reading and writing, it rather means the ability to communicate through multiple modes. Hence, it is important to embed multimodality (the study of using multiple modes) in educational settings